Percutaneous 17ß-estradiol replacement therapy in hypertensive postmenopausal women - Osório-Wender,M.C. (1997)
The present study evaluated the short-term effects of percutaneous 17ß-estradiol on blood pressure, metabolic profile and hormonal levels in postmenopausal women with systemic arterial hypertension. After a wash-out period of 15 days, 10 hypertensive patients were treated with guanabenz acetate to control blood pressure, followed by 17ß-estradiol in the form of hydroalcoholic gel administered for 21 of 28 days of each cycle, for 3 cycles. Patients were evaluated before, during and 2 months after estrogen administration. Systolic and diastolic blood pressure or heart rate did not present any significant change in any patient when compared to those periods with the antihypertensive drug only (pretreatment period and 60 days after estrogen therapy was discontinued). Plasma biological markers of hepatic estrogenic action (plasma renin activity, antithrombin III, triglycerides, total cholesterol and lipoproteins) also remained unchanged during the study. Hormone treatment was effective, as indicated by the relief of menopausal symptoms, a decrease in FSH levels (73.48 ± 27.21 to 35.09 ± 20.44 IU/l, P<0.05), and an increase in estradiol levels (15.06 ± 8.76 to 78.7 ± 44.6 pg/ml, P<0.05). There was no effect on LH (18.0 ± 9.5 to 14.05 ± 8.28 IU/l). Hormone levels returned to previous values after estrogen treatment was discontinued. The data indicate that short-term percutaneous 17ß-estradiol replacement therapy, at the dose used, seems to be a safe hormone therapy for hypertensive menopausal women. Nevertheless, a controlled, prospective, randomized clinical assay with a larger number of subjects is needed to definitely establish both the beneficial and harmful effects of hormone replacement therapy in hypertensive women